Enhancing English Writing Ability in Chinese Lower-Secondary Students through Indirect Corrective Feedback and Metalinguistic Corrective Feedback. - Liu, Yuxin; Sukavatee, Pornpimol (An Online Journal of Education, 2023)
This study primarily aims to examine the distinct effects of indirect and metalinguistic corrective feedback on the English writing abilities of lower-secondary Chinese students. Additionally, the study seeks to explore students' viewpoints regarding these two types of feedback, focusing on their preferences and comprehension of feedback mechanisms. The participants included 30 Grade 8 students from a public school in Rizhao City, Shandong Province, China. The instruments for collecting data included a pre-test, a post-test, and interview questions. The quantitative results of the two-way repeated-measures ANOVA revealed that the difference between the two types of feedback is insignificant. The interview results revealed that students preferred metalinguistic corrective feedback because it was easier to understand. The research highlights the value of providing different types of corrective feedback to students. Teachers can tailor their feedback based on individual student needs and preferences.